Synthesis of [18F]FMISO, a hypoxia-specific imaging probe for PET, an overview from a radiochemist's perspective - Torsten Kniess; Jörg Zessin; Peter Mäding; Manuela Kuchar; Oliver Kiss; Klaus Kopka (SpringerOpen, 2023)
Abstract Background [18F]fluoromisonidazole ([18F]FMISO, 1H-1-(3-[18F]fluoro-2-hydroxypropyl)-2-nitroimidazole) is a commonly used radiotracer for imaging hypoxic conditions in cells. Since hypoxia is prevalent in solid tumors, [18F]FMISO is in clinical application for decades to explore oxygen demand in cancer cells and the resulting impact on radiotherapy and chemotherapy. Results Since the introduction of [18F]FMISO as positron emission tomography imaging agent in 1986, a variety of radiosynthesis procedures for the production of this hypoxia tracer has been developed. This paper gives a brief overview on [18F]FMISO radiosyntheses published so far from its introduction until now. From a radiopharmaceutical chemist's perspective, different precursors, radiolabeling approaches and purification methods are discussed as well as used automated radiosynthesizers, including cassette-based and microfluidic systems. Conclusion In a GMP compliant radiosynthesis using original cassettes for FASTlab we produced [18F]FMISO in 49% radiochemical yield within 48 min with radiochemical purities > 99% and molar activities > 500 GBq/µmol. In addition, we report an easy and efficient radiosynthesis of [18F]FMISO, based on in-house prepared FASTlab cassettes, providing the radiotracer for research and preclinical purposes in good radiochemical yields (39%), high radiochemical purities (> 99%) and high molar activity (> 500 GBq/µmol) in a well-priced option.